Parkinson's Disease Skin Fibroblasts Display Signature Alterations in Growth, Redox Homeostasis, Mitochondrial Function, and Autophagy - Teves, Joji M. Y.; Bhargava, Vedanshi; Kirwan, Konner R.; Corenblum, Mandi J.; Justiniano, Rebecca; Wondrak, Georg T.; Anandhan, Annadurai; Flores, Andrew J.; Schipper, David A.; Khalpey, Zain; Sligh, James E.; Curiel-Lewandrowski, Clara; et al. (Frontiers in Neuroscience, 2018)
The discovery of biomarkers for Parkinson’s disease (PD) is challenging due to the heterogeneous nature of this disorder, and a poor correlation between the underlying pathology and the clinically expressed phenotype. An ideal biomarker would inform on PD-relevant pathological changes via an easily assayed biological characteristic, which reliably tracks clinical symptoms. Human dermal (skin) fibroblasts are accessible peripheral cells that constitute a patient-specific system, which potentially recapitulates the PD chronological and epigenetic aging history. Here, we compared primary skin fibroblasts obtained from individuals diagnosed with late-onset sporadic PD, and healthy age-matched controls. These fibroblasts were studied from fundamental viewpoints of growth and morphology, as well as redox, mitochondrial, and autophagic function. It was observed that fibroblasts from PD subjects had higher growth rates, and appeared distinctly different in terms of morphology and spatial organization in culture, compared to control cells. It was also found that the PD fibroblasts exhibited significantly compromised mitochondrial structure and function when assessed via morphological and oxidative phosphorylation assays. Additionally, a striking increase in baseline macroautophagy levels was seen in cells from PD subjects. Exposure of the skin fibroblasts to physiologically relevant stress, specifically ultraviolet irradiation (UVA), further exaggerated the autophagic dysfunction in the PD cells. Moreover, the PD fibroblasts accumulated higher levels of reactive oxygen species (ROS) coupled with lower cell viability upon UVA treatment. In essence, these studies highlight primary skin fibroblasts as a patient-relevant model that captures fundamental PD molecular mechanisms, and supports their potential utility to develop diagnostic and prognostic biomarkers for the disease.